Antimicrobial activity evaluation of residual orange oil (UNED Research Journal, 2018)
The residue of the orange peel is a common contaminant in Mexico, even though it can be used in the cosmetic, pharmaceutical and food areas. We extract orange oil from residual skin, and determine its chemical compounds and antimicrobial activity. We used Soxhlet distillation, liquid-liquid extraction and pressing extraction, and gas chromatography coupled to mass spectrometry (GC-MS). We used a modified Kirby & Bauer technique on Acremonium sp., Alternaria sp., Aspergillus niger, Candida albicans, Pseudomonas aeruginosa ATCC27853, Staphylococcus aureus ATCC 25923, Trichoderma sp. and Verticillium sp. The Soxhlet method was the most efficient (2,065%). We observed inhibition values of 75% to 100% for S. aureus and P. auroginosa; 75 to 100% for Candida albicans; and 50 to 74% for Pseudomonas auroginosa. It acted as fungistatic for all strains. The CG-MS profile was: D-limonene 85,93%, β-myrcene 2,23%, linalool 1,72%, decanal 0,63%, α-pinene 0,43% and sabinene 0,20% per μL of oil per Head-space and per direct injection (main components: alkanes, and perilic alcohol, D-limonene and linalool).
Keywords: Inhibition; microorganisms; oil; orange; waste.